Zvi – Reactive Barriers for the Remediation of Soils Polluted with Clopyralid: Are They Really Worth? - Salazar-Gonzalez, R; Vidal-Fuentes, J; Vidal-Fuentes, J (Elsevier B.V., 2018)
In this work, the remediation of soil spiked with clopyralid is evaluated using two types of zero valent iron (ZVI) barriers coupled with electrokinetic soil flushing (EKSF). These barriers consist of soil merged with iron particles. In one of the tests conducted, granular milimetric iron was used, whereas in the other, iron was placed in the form of nanoparticles. The performance of this novel technology is compared to that of single EKSF technology. Tests were carried out in bench scale mockups (175 L) and they lasted one month. Over this period, soil underwent the application of an electric field of 1.0 V/cm between a row of three anodes and a row of three cathodes. Results indicate that ZVI barriers seriously affect electrokinetic flushes by preventing the mobility of pollutants to the electrode wells. However, they achieve a larger dehalogenation of clopyralid than single EKSF. There are no significant differences between the results obtained using the two sizes of ZVI and the volatilization of pollutants associated to thermal effects was almost prevented by means of capillary barriers implemented on top of the mockups. After the treatment, most of the clopyralid not removed is concentrated near the anodes wells and a very important fraction can be easily extracted by excavating a very small percentage of the soil, because the pollutant has been concentrated in very specific points during remediation. Results are significant for the design of full-scale applications for the remediation of soils polluted with soluble chlorinated hydrocarbons. © 2018 Elsevier B.V.